2012
DOI: 10.1093/humrep/des280
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the influence of vitamin D levels on IVF outcomes

Abstract: Vitamin D deficiency is associated with lower pregnancy rates in non-Hispanic whites, but not in Asians, possibly due to their lower IVF success rates. Vitamin D deficiency was not correlated with ovarian stimulation parameters or with markers of embryo quality, suggesting its effect may be mediated through the endometrium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
106
1
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(131 citation statements)
references
References 28 publications
12
106
1
12
Order By: Relevance
“…As was posited in studies of nondonor IVF patients by Ozkan et al [69], Polyzos et al [73] and the previous Rudick et al [70] publication, this study indicates that the effects of vitamin D are likely at the level of the endometrium. While these previous studies in nondonor IVF patients were mostly speculative in this regard, by using the oocyte donorrecipient model, Rudick et al [71] directly evaluated the role of the endometrium and its impact on implantation, and is consistent with the postulate that vitamin D modulates NK cell activity.…”
Section: Systematic Review On Effects Of Vitamin D On Art Outcomessupporting
confidence: 70%
See 3 more Smart Citations
“…As was posited in studies of nondonor IVF patients by Ozkan et al [69], Polyzos et al [73] and the previous Rudick et al [70] publication, this study indicates that the effects of vitamin D are likely at the level of the endometrium. While these previous studies in nondonor IVF patients were mostly speculative in this regard, by using the oocyte donorrecipient model, Rudick et al [71] directly evaluated the role of the endometrium and its impact on implantation, and is consistent with the postulate that vitamin D modulates NK cell activity.…”
Section: Systematic Review On Effects Of Vitamin D On Art Outcomessupporting
confidence: 70%
“…Only eight of the 34 articles retrieved from PubMed met criteria (Fig. 2) [66][67][68][69][70][71][72][73]. Reference lists of chosen studies and narrative reviews were cross-referenced to find additional studies.…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…In a cross sectional study of infertile women undergoing IVF, we had previously identified significantly higher levels of 25-hydroxyvitamin D (25OHD), a metabolite that reliably reflects the overall vitamin D status, in the follicular fluid of women achieving clinical pregnancy following IVF [23]. While this latter observation was recently corroborated by others [24], including in donor egg recipients [25], data relating vitamin D status to IVF outcome remain far from unequivocal [26].…”
Section: Introductionmentioning
confidence: 92%